The role of lifestyle change in health promotion - GHEORGHE, Mirela Manuela; CRINGANU, George Mădălin; ZHANG, Juan (Annals of Spiru Haret University. Economic Series, 2015)
We are experiencing a period where we are faced with rising healthcare costs, as well as an increased disease impact on the entire population of the country. Although the slogan “prevention is cheaper than cure” may seem old-fashioned, however, it is more true than ever. It is necessary to offer health education and also to promote health care in Romania, in accordance with the international standards, as adopted by the European Union. Health Promotion is the art and science of helping people change their lifestyle in order to achieve a state of optimal health, restoring the harmony at all levels of human existence. Promoting a lifestyle which given certain conditions maximizes health, welfare and human fulfilment represents a goal that does not belong exclusively to the health sector; all fields of activity, all those sectors that define the life of an individual or a community are essential parts of achieving a healthy lifestyle. Modern men adopt a lifestyle where sedentary life, overeating, smoking, erratic working hours and alcohol use are common behaviours. Therefore, they become vulnerable to a new class of diseases of multi-factorial aetiology where the lifestyle plays a prominent role. Although the lifestyle may be complex, it is still under personal control and lead by the ability to choose extensively, which can be of benefit to the person’s life and health. Choices regarding health involve more than objective information. Health education should be an ongoing concern for health professionals and health educators, psychologists, sociologists, family, for those who through effective collaboration contribute to ensuring physical and mental health in the community, in the increasingly demanding conditions of the modern life, which raise difficult issues regarding human adaptability.